EFFECT OF MUSTAKADI VATI IN THE MANAGEMENT OF GRAHANI DOSHA IN CHILDREN – A CASE STUDY (AYUSHDHARA, 2019)
BACKGROUND: Grahani is the Adhishthana of Agni and Agni Dushti is the main reason of the disease. The disease Grahani Dosha is very commonly seen in present pediatric practice and it aggravates to form a critical condition if the proper care is not taken.MATERIAL AND METHOD: A 8-years-old male patient of Grahani Dosha with complaints of defecation just after taking meal, Bowel frequency 3-4 times/day, irregular bowel habit, loss of appetite, generalized weakness, occasional pain in abdomen, slow weight gain for 5-6 months was treated by Mustakadi Vati in three divided doses of 10 Vati per day after meal for 8 weeks with SukhoshnaJala.RESULT: Marked improvement was found after 8 weeks of treatment i.e., bowel frequency reduced to 1 time/day, no weakness, abdominal pain relieved, 2 kg body weight gained. Hematological parameters along with routine and microscopic investigations of stool and urine were done before and after the treatment, all were found normal. Mala Parikshana was done before treatment which showed sinking of stool in water and foul smell and after 8 weeks of treatment again Mala Parikshana was done where floating of stool in water and no foul smell were found.CONCLUSION: This case study has shown that Mustakadi Vati is effective in improving the symptoms of Grahani Dosha. Marked improvements were found in all the symptoms of Grahani Dosha in Children.